Strategic Approach to the Splenic Artery in Laparoscopic Spleen-preserving Distal Pancreatectomy. Issue 4 (August 2015) - Inoko, Kazuho; Ebihara, Yuma; Sakamoto, Keita; Miyamoto, Noriyuki; Kurashima, Yo; Tamoto, Eiji; Nakamura, Toru; Murakami, Soichi; Tsuchikawa, Takahiro; Okamura, Keisuke; Shichinohe, Toshiaki; Hirano, Satoshi
<x xml:space="preserve">Abstract</x> Background: Laparoscopic spleen-preserving distal pancreatectomy (LSPDP) is an ideal procedure in selected patients with benign or low-grade malignant tumors in the body/tail of the pancreas. We describe our procedure and experience with splenic vessel-preserving LSPDP (SVP-LSPDP) in a retrospective case series. Methods: Six consecutive patients underwent SVP-LSPDP from January 2011 to September 2013. We evaluated the courses of the splenic artery by preoperative computed tomography and applied an individualized approach (the superior approach or inferior approach) to the splenic artery. Results: All of the operations were successful. The median surgical duration was 249 minutes. The median blood loss was 0 mL. Pathologic examination revealed 4 cases of insulinoma, 1 case of solid pseudopapillary tumor, and 1 case of pancreatic metastasis from renal carcinoma. Conclusions: In performing SVP-LSPDP, it is effective to make a strategic choice between 2 different approaches according to the course of splenic artery.